Strategi daya tindak sebagai moderator dalam hubungan antara kecerdasan emosi dengan kepuasan kerja, komitmen organisasi dan kesejahteraan psikologi - Yaacob, Mardhiah (2012)
This study is to identify the effect of emotional intelligence towards job satisfaction, organizational commitment and psychological well-being among staffs in Ibu Pejabat Polis Kontinjen, Melaka. Besides, this study also identify the effect of coping strategies as moderator in relationship between emotional intelligence with job satisfaction, organizational commitment and psychological well-being. This study focused on four component emotional intelligence which is perceiving emotion, using emotion, understanding emotion and management emotion and three component organizational commitment which is affective commitment, continuence commitment and normatic commitment. The data was collected from 252 respondents by using a questionnaire were distributed to staffs at Ibu Pejabat Polis Kontinjen, Melaka. The data were analyzed using SPSS version 16.0. The data were analyzed using Pearson correlation, multiple regression and hierarchical regression. The findings revealed that most of the respondents showed high emotional intelligence. There is a positive and significant relationship between emotional intelligence with job satisfaction, organizational commitment and psychological well-being. Perceiving emotion significantly can influence organizational commitment while understanding emotion significantly can influence job satisfaction and psychological well-being. The findings also revealed that component using emotion and management emotion were not influence job satisfaction, organizational commitment and psychological well-being. Besides, this study affirms that the higher perceiving emotion meaning higher job satisfaction and affective commkitment among respondents with high coping strategies. While, coping strategis are not acting as moderator in relationship between emotional intelligence with continuence commitment, normative commitment and psychological well-being.